Breast reconstruction for locally advanced breast cancer previously submitted to mastectomy and an ipsilateral thoracoabdominal dermofat (ITADE) flap - Da Costa Vieira, René Aloisio [UNESP]; Ching, An Wan; De Oliveira-Junior, Idam [UNESP] (SAGE Publications, 2023)
Thoracoabdominal (TA) flaps are a good option for primary closure of small and medium defects after mastectomy for locally advanced breast tumours. Although they have a higher rate of necrosis than myocutaneous flaps, they can be easily performed by breast surgeons. Few studies on this procedure have been reported, and we have been unable to identify any prior publications reporting breast reconstruction with TA flaps.
Keywords: Breast cancer; locally advanced tumors; myocutaneous flaps; surgical flaps